Characterization of Hemerocallis citrina Transcriptome and Development of EST-SSR Markers for Evaluation of Genetic Diversity and Population Structure of Hemerocallis Collection - Li, Sen; Ji, Fangfang; Hou, Feifan; Cui, Huliang; Shi, Qingqing; Xing, Guoming; Weng, Yiqun; Kang, Xiuping (Frontiers in Plant Science, 2020)
Hemerocallis spp. commonly known as daylilies and night lilies, are among the most popular ornamental crops worldwide. In Eastern Asia, H. citrina is also widely cultivated as both a vegetable crop and for medicinal use. However, limited genetic and genomic resources are available in Hemerocallis. Knowledge on the genetic diversity and population structure of this species-rich genus is very limited. In this study, we reported transcriptome sequencing of H. citrina cv. ‘Datonghuanghua’, which is a popular, high-yielding variety in China. We mined the transcriptome data, identified and characterized the microsatellite or simple sequence repeat (SSR) sequences in the expressed genome. From ~14.15 Gbp clean reads, we assembled 92,107 unigenes, of which 41,796 were annotated for possible functions. From 41,796 unigenes, we identiﬁed and characterized 3,430 SSRs with varying motifs. Forty-three SSRs were used to fingerprint 155 Hemerocallis accessions. Clustering and population structure analyses with the genotypic data all placed the 155 accessions into two main groups corresponding to the nigh lily and daylily, respectively. The night lily group included accessions primarily from H. citrina, H. lilioasphodelus, and H. minor, the majority of which bloom in the evening/night, whereas the ~100 accessions in the day lily group bloom in the early morning. The utility of these SSRs was further exemplified in genome-wide association analysis of blooming time among these accessions. Twelve SSRs were found to have significant associations with this horticulturally important trait.